Correlation between QT Interval with Left Ventricular Mass Index (Using M-Mode Echocardiography) and Blood Pressure in Patients with Hypertension (Medico Legal Update, 2020)
Background: In patients with hypertension, the excessive blood pressure load correlates with neurohormonalactivities and will lead to left ventricular remodeling. QT interval often occurs in patients with hypertension.The correlation between structural changes and repolarization remains unclear.Method: This study involved 62 patients with hypertension (38 female and 24 male) to whom blood pressure,electrocardiogram and echocardiography examination were performed simultaneously. The correlationbetween QT interval with left ventricle mass index and blood pressure was statistically analyzed usingPearson correlation test.Results: The mean of QTc interval in patients with hypertension was 390.40±30.73 millisecond. Based onthe echocardiography examination results, the mean of left ventricular mass index was 75.38±12.36 withRWT of 0.36±0.06. Pearson correlation statistical analysis shows a correlation between QTc interval withleft ventricular mass index (r=0.277; p value=0.030) and systolic blood pressure (r=0.317; p value=0,014).Conclusion: QT interval correlated with increased left ventricular mass index and systolic blood pressure inhypertension patients with normal geometry and concentric remodeling.